越南学生汉语习得中的声母偏误分析 - Trần Thị Hải Yến; thuy cai; Huỳnh Bích Ngọc (Universitas Tanjungpura, 2023)
学习汉语的越南人不断增多。与其他国家的学生相比，越南学生更有学习汉语的优势。之所以这样说是因为在词汇方面越南语受了汉语的很大影响；语法方面跟汉语也很相似；再说，越南语也是有声调的一种语言。但另一方面，由于汉语与越南语只是相似，而并不完全相同，因此，越南学生学习起来也难免出现各种各样的偏误。而在越南学生的各种偏误中，笔者们认为语音偏误最为明显。特别是在越南学生对汉语声母的习得中,越南语的干扰对发音的影响最明显。因此，笔者试图进行调查研究，找出偏误的规律，并运用理论基础来对偏误进行解释，从而探讨偏误的成因，以便找出克服的方案以及提出教学建议。More and more Vietnamese are learning Chinese. Compared with students from other countries, Vietnamese students have more advantages in learning Chinese. This is because Vietnamese has been heavily influenced by Chinese in terms of vocabulary; The grammar is also very similar to Chinese; Besides, Vietnamese is a tonal language. But on the other hand, because Chinese and Vietnamese are only similar, but not exactly the same, so Vietnamese students will inevitably appear a variety of errors in learning. Among all kinds of errors of Vietnamese students, the authors think phonetic errors are the most obvious. Especially in the acquisition of Chinese initials by Vietnamese students, Vietnamese interference has the most obvious influence on pronunciation. Therefore, the author tries to conduct investigation and research to find out the law of the bias, and use the theoretical basis to explain the bias, so as to explore the causes of the bias, in order to find out the solution and put forward teaching suggestions.